2012
DOI: 10.1371/journal.pone.0050269
|View full text |Cite|
|
Sign up to set email alerts
|

Population Differentiation of Southern Indian Male Lineages Correlates with Agricultural Expansions Predating the Caste System

Abstract: Previous studies that pooled Indian populations from a wide variety of geographical locations, have obtained contradictory conclusions about the processes of the establishment of the Varna caste system and its genetic impact on the origins and demographic histories of Indian populations. To further investigate these questions we took advantage that both Y chromosome and caste designation are paternally inherited, and genotyped 1,680 Y chromosomes representing 12 tribal and 19 non-tribal (caste) endogamous popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 52 publications
3
19
1
Order By: Relevance
“…3), clearly demonstrates the findings of allele frequency patterns from South Asian Afghanistan - V, Caucasian - VI and South Indian Andhra Pradesh - VII as an “Other than Africa” split among 45 GAHPs for GST M1-T1 null genotypes with respect to their geographical distribution. This observation of other than Africa split in this study has been reported here in agreement to the concepts of later migration of the populations in regions other than Africa [60, 64]. In conclusion, the data of seven patterns for GST M1-T1 null allele frequency from Xhosa tribe (I), Zimbabwe (II), Ethiopia (III), Egypt (IV), Afghanistan (V), Caucasian (VI) and South Indian Andhra Pradesh (VII) reported in this study compare constructively with the earlier studies that suggested the PAs of relatively recent origin show comparatively small genetic differences and high genetic affinity among them [11, 46, 52, 58].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…3), clearly demonstrates the findings of allele frequency patterns from South Asian Afghanistan - V, Caucasian - VI and South Indian Andhra Pradesh - VII as an “Other than Africa” split among 45 GAHPs for GST M1-T1 null genotypes with respect to their geographical distribution. This observation of other than Africa split in this study has been reported here in agreement to the concepts of later migration of the populations in regions other than Africa [60, 64]. In conclusion, the data of seven patterns for GST M1-T1 null allele frequency from Xhosa tribe (I), Zimbabwe (II), Ethiopia (III), Egypt (IV), Afghanistan (V), Caucasian (VI) and South Indian Andhra Pradesh (VII) reported in this study compare constructively with the earlier studies that suggested the PAs of relatively recent origin show comparatively small genetic differences and high genetic affinity among them [11, 46, 52, 58].…”
Section: Discussionsupporting
confidence: 93%
“…2 and 3) has been reported as pattern - V for GST M1-T1 null genotypes in accordance to the reports of various authors [60, 62, 64]. Further, population in Pakistan (South Asia) has been reported with Afghanistan (South Asia) pattern for GST M1-T1 null allele frequency (Table 3) in this study, though it was found with genetic affinity to PAs from Mongolia (East Asia), Europe (South, East and West) and Andhra Pradesh (South India) in corroborate to the earlier reports of Templeton (2002), who stated the findings of considerable overlap among East Asians, Europeans and South Indian populations [64].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, this claim should not be considered exclusively to establish the fact that Dravidian populations of India originated in west Asia and then migrated to south India (Sengupta et al 2006). The co-presence of these west Eurasian mtDNA and Y-chromosome haplogroups in Dravidianspeaking tribal and caste groups in South India suggest that their spread is not associated with the Indo-Aryan migration (Arunkumar et al 2012). A large proportion of the west Eurasian mtDNA haplogroups observed among the higher-ranked caste groups, their phylogenetic affinity and age estimate indicate recent Indo-Aryan migration to India from west Asia.…”
Section: Resultsmentioning
confidence: 99%
“…A closest neighbour analysis in the phylogeny showed that Indian populations have an affinity towards Southern European populations and that the time of divergence from these populations substantially predated the Indo-European migration into India, probably reflecting ancient shared ancestry rather than the Indo-European migration, which had little effect on Indian male lineages. Among the tribal 2004; Metspalu et al 2004;Sahoo et al 2006;Thanseem et al 2006;Sengupta et al 2006;ArunKumar et al 2012), and autosomes (Reich et al 2009;Metspalu et al 2011;Moorjani et al 2013;Juyal et al 2014;Basu et al 2015). Till recently, the Y-chromosome analysis mostly relied on calculating frequencies of pre-defined haplogroups, and the time and place of origin have been estimated for some of these.…”
Section: Introductionmentioning
confidence: 99%